PEMETAAN PENELITIAN AKUNTANSI BELA NEGARA DAN PENGELOLAAN KEUANGAN PADA ORGANISASI NIRLABA: SEBUAH STUDI BIBLIOMETRIK - Firnanda, Puspita Dwi; Yuhertiana, Indrawati (Unitri Press, 2025)
This study aims to analyze the development of research on fund or financial management in non-profit organizations using bibliometric analysis methods utilizing VOSviewer software. The data used is taken from scientific publications sourced from Google Scholar. The results of the analysis show that the topics of accountability and financial transparency in nonprofit organizations have become a trend and have been widely studied, while specific research on financial management and the need for implementing national defense accounting in mosque is is still rare. Thise research can provide insight to encourage further research related to the development of practices in mosque financial management based on national defense accounting principles. In addition, this study is expected to contribute to improving the financial management system in others non-profit sector.